Effect of combined pneumococcal conjugate and polysaccharide vaccination on recurrent otitis media with effusion - van Heerbeek, Niels; Straetemans, Masja; Wiertsema, Selma P; Ingels, Koen J A O; Rijkers, Ger T; Schilder, Anne G M; Sanders, Elisabeth A M; Zielhuis, Gerhard A (Pediatrics (Evanston), 2006)
Otitis media with effusion (OME) is very common during childhood. Because Streptococcus pneumoniae is one of the most common bacterial pathogens involved in OME, pneumococcal vaccines may have a role in the prevention of recurrent OME. We sought to assess the effect of combined pneumococcal conjugate and polysaccharide vaccinations on the recurrence of OME. A randomized, controlled trial was performed with 161 children, 2 to 8 years of age, with documented persistent bilateral OME. All subjects were treated with tympanostomy tubes (TTs). One half of the subjects were assigned randomly to additional vaccination with a 7-valent pneumococcal conjugate vaccine 3 to 4 weeks before and a 23-valent pneumococcal polysaccharide vaccine 3 months after tube insertion. Blood samples were drawn at the first vaccination, at the time of TT placement, and 1 and 3 months after the second vaccination. Levels of IgA and IgG serum antibody against the 7-valent pneumococcal conjugate vaccine serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F were measured with enzyme-linked immunosorbent assays. All children were monitored for recurrence of OME for 6 months after spontaneous extrusion of the TTs. The overall recurrence rate of bilateral OME was 50%. Pneumococcal vaccinations induced significant 4.6- to 24.4-fold increases in the geometric means of all conjugate vaccine serotype antibody titers but did not affect recurrence of OME. Combined pneumococcal conjugate and polysaccharide vaccination does not prevent recurrence of OME among children 2 to 8 years of age previously known to have persistent OME. Therefore, pneumococcal vaccines are not indicated for the treatment of children suffering from recurrent OME.